An Analysis of Zakat Implementation from the Perspective of Islamic Jurisprudence as an Instrument for Economic Equality and Social Justice - Sugih Nugraha; Hudallah Hudallah (Penerbit Hellow Pustaka, 2025)
This paper illustrates that the basic concepts and principles of zakat from the perspective of Islamic jurisprudence are the main foundation in the implementation of this teaching. Recognized types of zakat, such as zakat mal and zakat fitrah, play an important role in creating social justice. The process of calculating and distributing zakat requires a deep understanding so that the goals of community welfare can be achieved. Zakat, with the function of reducing economic inequality, acts as a tool to create fair social balance. However, inhibiting factors, including ignorance and institutional constraints, can influence the effectiveness of zakat implementation in society. In the context of its impact on social development and welfare of the people, zakat has great potential to advance society and create a just environment.